(untitled) (Indian Journal of Child Health, 2020)
Background: Population specific, systematic comprehensive strategies are needed to reduce the morbidity and mortality of the neonates at the national level. Neonatal age group usually contributes to a major disease burden. Objective: The objective of the study was to identify the morbidity and mortality patterns in our neonatal tertiary care referral center. Materials and Methods: This was a prospective observational study done over a period of 1 year, 1 month from January 2019 to January 2020. Results: Admissions in early 7 days were more at 86.4% to after 7 days at 13.6%. Males were 50.9% with almost equal to female population 49.1%; preterm and low birth weight (LBW) babies were 49.3% and 49.75%, respectively, and term babies more than 2.5 kg babies were 50.7% and 51.25%. The LBW babies were admitted about 28.07% and 26.98% inborn and outborn babies. In preterm babies, more babies admitted in 34 weeks–37 weeks gestational age, 16.50% and 15.56% in inborn and outborn babies, respectively. As per morbidity profile, in inborn babies, the common reasons for admission were respiratory distress 22.09% and neonatal jaundice contributing about 22.03%. The common causes of admission in outborn were sepsis which was 27.45% and hypoxic ischemic encephalopathy which was contributing about 20%. Conclusion: In our study, we found that major portion of the babies were preterm and LBW babies. This shows changing trend toward preterm delivery. It is good in the sense of antenatal steroid coverage which was 80–90% but antenatal magnesium sulfate covered in 39% outborn babies only. Prematurity, infections, asphyxia, and neonatal jaundice were the leading cause of admissions into our neonatal unit.